Adherence and variability in warfarin dose requirements: assessment in a prospective cohort. (January 2013) - Jorgensen, Andrea L; Hughes, Dyfrig A; Hanson, Anita; van Eker, Diane; Toh, Cheng Hock; Pirmohamed, Munir; Williamson, Paula R
Aim: Although several genetic and nongenetic factors are associated with warfarin dose, approximately 40% of variability remains unexplained. An as yet unexplored factor is medication adherence. Here, we investigate the influence of adherence on response to warfarin and on pharmacogenetic analyses of association.Patients & methods: A total of 311 patients starting warfarin were followed-up prospectively, and adherence was measured at 1, 8 and 26 weeks. The association between adherence and warfarin response was tested, and the additional proportion of variability in response explained by adherence was assessed.Results: Significant associations were found between adherence and achievement of stable dose and time taken to achieve it, with nonadherers taking longer. Adjusting for adherence increased the proportion of explained variability in treatment response by up to 8%.Conclusion: Given the significant contribution of adherence to drug response, we recommend that consideration is given to the value of assessing adherence when designing future pharmacogenetic studies of warfarin and other drugs. Original submitted 19 July 2012; Revision submitted 26 November 2012